2017
DOI: 10.1038/srep46514
|View full text |Cite
|
Sign up to set email alerts
|

IFNβ Protects Neurons from Damage in a Murine Model of HIV-1 Associated Brain Injury

Abstract: Infection with human immunodeficiency virus-1 (HIV-1) causes brain injury. Type I interferons (IFNα/β) are critical mediators of any anti-viral immune response and IFNβ has been implicated in the temporary control of lentiviral infection in the brain. Here we show that transgenic mice expressing HIV-1 envelope glycoprotein 120 in their central nervous system (HIVgp120tg) mount a transient IFNβ response and provide evidence that IFNβ confers neuronal protection against HIVgp120 toxicity. In cerebrocortical cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 84 publications
3
51
0
Order By: Relevance
“…The gene expression pattern indicative of a type I IFN signature was in accordance with an earlier report of IFN-stimulated gene (ISG)-15 in the brain of HIVgp120tg mice (Wang et al , 2012). A recent follow-up study confirmed that GFAP-gp120tg mice mounted a transient IFNβ response around 1.5 months of age (Thaney et al , 2017). While the mRNA expression for IFNβ had returned to baseline in 3 and 6 months-old animals, the signature of IFN-stimulated genes remained detectable.…”
Section: Research Topics and Studies Using Gfap-hivgp120tg Micementioning
confidence: 89%
See 3 more Smart Citations
“…The gene expression pattern indicative of a type I IFN signature was in accordance with an earlier report of IFN-stimulated gene (ISG)-15 in the brain of HIVgp120tg mice (Wang et al , 2012). A recent follow-up study confirmed that GFAP-gp120tg mice mounted a transient IFNβ response around 1.5 months of age (Thaney et al , 2017). While the mRNA expression for IFNβ had returned to baseline in 3 and 6 months-old animals, the signature of IFN-stimulated genes remained detectable.…”
Section: Research Topics and Studies Using Gfap-hivgp120tg Micementioning
confidence: 89%
“…Moreover, a peripheral immune challenge with recombinant gp160 triggered a strong lymphocyte-mediated immune response and infiltration of the brain only in gp120tg animals, but not non-tg littermate controls or in GFAP-LacZ tg mice, thus providing indirect evidence for the presence of viral envelope protein in the CNS of gp120tg mice (Toggas and Mucke, 1998). Several subsequent studies included an additional GFAP-gp120tg founder line that expresses more easily detectable envelope protein levels and therefore is called gp120tg H igh P rotein E xpressor, (HPX) line (Garden et al , 2002; Lee et al , 2011; Maung et al , 2014; Thaney et al , 2017; Toggas and Mucke, 1996). The studies discussed here served at least one of two purposes: either improving our understanding of the neuropathological mechanism(s) of HIV infection, or exploring potential future therapies for NeuroAIDS and HAND.…”
Section: Hiv-1 Gp120-transgenic Mice As An Animal Model In Neuroaids mentioning
confidence: 99%
See 2 more Smart Citations
“…IFNb is induced in the CNS during many neurotropic infections, including WNV, La Crosse virus, HIV, and HSV-1 (9,33,70,130,136). IFNb signaling is crucial for viral control in the brain for WNV and HSV-1 infections, and may be neuroprotective and limit viral replication during HIV infection of the CNS (9,10,70,119,130). HSV-infected NSPCs can produce IFNb, suggesting that the NSPCs may have an autocrine response to IFNb (114).…”
Section: Interferon Betamentioning
confidence: 99%